C.A.R.I.N.G: A Conceptual Model for Promoting Student Well-Being - Jeffrey A. Russell; Kellee R. Vess (Adult Education Research Conference, 2014)
From our own experiences as educators, we found that many college students seemed overwhelmed and stressed from a myriad of academic and personal responsibilities. The C.A.R.I.N.G. model provides a new lens for promoting student well-being through the utilization of adult learning principles.